Eco-friendly sandwich panel based on bottle caps core and sustainable components: Static and dynamic characterisation - Pablo Resende Oliveira; Sebastian Kilchert; Michael May; Tulio Hallak Panzera; Fabrizio Scarpa; Stefan Hiermaier (Composites Part C: Open Access, 2020)
A sandwich structure made of sustainable components is investigated under quasi-static and dynamic conditions. The upcycled plastic bottle caps are used to manufacture a greener circular cell honeycomb core, based on a full factorial design. A recycled PET foil is used as skins, being compared to a classic panel with aluminium skins. The particle-reinforced adhesive is also tested by adding recycled rubber particles, from remoulded tyres, and cement particles. Three-point bending test and a low-velocity drop-tower test are performed on sandwich structures. Flexural modulus has a 19% increase with aluminium skins, while core shear modulus increases by 27% with cement-reinforced PET panels. Energy absorption in quasi-static tests increased by 26% with rubber inclusions in aluminium-based samples, while no significant effect is observed in low-velocity impact tests. Aluminium skins lead to increments of up to 198% for specific energy absorption and 298% for specific maximum load under impact. The satisfactory results of the static and dynamic characterisation of the bottle cap structure highlight the promising characteristic of the reuse of plastic waste in lightweight structural applications.